METODE PERUMUSAN STRATEGI PERUSAHAAN ASURANSI UNTUK PENCAPAIAN TARGET PERUSAHAAN - Ranny Dwi Anggraini (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2015)
In this day, each insurance company has many products offered to consumers in order toachieve its targets. However, because a lot of competition in the insurance industry so that not allcompanies make profits. Based on that, the fundamental problem faced is how to formulate a strategyin accordance with the company's environmental conditions so that the desired target is reached. Thepurpose of this research is to formulate a strategy in accordance with the conditions of the company.The method used consists of 3 stages of strategy formulation is the input stage, phase matching anddecision-making stage. The input stage using matrix EFE and IFE matrix, matching phase using matrixGrand Strategy and SWOT matrix and decision stage using pairwise comparison approach. There are3 alternatives chosen strategy of the research, that are market penetration with a weight of 0.5396,market development with a weight of 0.2970 and development of products with a weight of 0.1634.